THE USE OF SCANNING ELECTRON MICROSCOPY WITH MICROANALYSIS SYSTEM FOR THE STUDY OF QUALITY OF BRASS COATING - T. P. Kurenkova; V. I. Voznaya (Литьë и металлургия)
Possibilities of using a scanning electron microscope equipped with an microanalysis to study the quality of brass coating on the blank for the wire and steel cord production are shown.